Note on oscillation of neutral differential equations with multiple delays - Petr Hasil; Michal Pospíšil; Lucia Pospíšilová Škripková; Michal Veselý (Electronic Journal of Qualitative Theory of Differential Equations)
This note is a reaction on a recently published sufficient condition for oscillation of all solutions of a neutral delay differential equation. It is shown by a counterexample that the result is not correct and the problem is explained in details. Several, more general, classes of neutral differential equations with time-dependent discrete, distributed as well as mixed delays are considered. New sufficient conditions for oscillation of all their solutions are proved. Applications are given for illustration.